Catheter Associated Urinary Tract Infections: A Cross-sectional Study from a Tertiary Care Centre in Kerala, India - Thindiparembath Surendran Sushitha; Kundoly Velayudhan Suseela (National Journal of Laboratory Medicine, 2022)
Introduction: Catheter Associated Urinary Tract Infections (CAUTIs) are the commonest nosocomial infection and may lead to serious medical complications. An early detection and appropriate antimicrobial therapy based on antimicrobial susceptibility testing together with infection control practices play a key role in management of CAUTI. Aim: To identify the aetiological agents causing CAUTI and to understand the antimicrobial susceptibility pattern of the isolates. Materials and Methods: A prospective cross-sectional study was conducted in the Department of Microbiology of a tertiary care centre in Kerala, India for the duration of six months from JanuaryJune 2014. Urine samples were collected from patients with urinary catheters in situ for more than three days, admitted in Intensive Care Unit (ICU) and wards. Urine samples were subjected to wet mount, culture and susceptibility testing. Responsible pathogens and their antimicrobial susceptibility pattern were obtained by using Vitek 2 automated system based on Clinical and Laboratory Standards Institute (CLSI) standards. Data was analysed using the International Business Machines Statistical Package for the Social Sciences (IBM SPSS) version 27.0. Descriptive analysis was used. Results: Among 150 catheterised patients included, 36 cases (24%) developed CAUTI. The overall rate of CAUTI was 7.03 per 1000 catheter days in present study. The gram negative bacilli were the major isolates comprising Enterobacteriaceae 32 (87.5%) and Non fermenters 4 (12.5%). Escherichia coli was the predominant 19 (53%) organism followed by Klebsiella pneumoniae, Pseudomaonas aeruginosa, Enterococcus faecalis. Extended Spectrum Beta Lactamase (ESBL) producing gram negative bacteria 19 (67.8%) were isolated. The isolates in CAUTI were found to be susceptible to cefoperazone sulbactam combination 21 (65.6%), amikacin 22 (68.7%), piperacillin+ tazobactam 24 (75%), nitrofurantoin 27 (84%), imipenem 27 (84%) and tigecycline 27 (96.4%). All were susceptible to colistin. The gram positive isolates were susceptible to nitrofurantoin 3 (75%), vancomycin and linezolid (both 100%). Conclusion: CAUTI is a preventable Hospital Acquired Infection (HAI) seen worldwide, but the incidence can be lowered by reducing the catheter procedures, the duration of catheterisation and taking aseptic precautions and by appropriate prophylactic antibiotics.